Azaboracyclooctatetraenes reveal that the different aspects of triplet state Baird‐aromaticity are nothing but different. (1st November 2022) - Preethalayam, Preethanuj; Proos Vedin, Nathalie; Radenković, Slavko; Ottosson, Henrik
Abstract: The Baird‐aromaticity of BN/CC cyclooctatetraene isosteres (azaboracyclooctatetraenes) in their lowest triplet states (T1 ) has been explored through computations of various aromaticity indices that describe the different aspects of aromaticity (magnetic, electronic, energetic and geometric). While cyclooctatetraene (COT ) is aromatic in its T1 state following Baird's 4 n rule, we now reveal that the degrees of Baird‐aromaticity of its BN/CC isosteres vary with aromaticity aspect considered. The thermodynamically most stable octagonal B4 N4 H8 isomer, having an alternating B and N pattern (borazocine, B 4 N 4 COT‐A ), is only weakly aromatic or nonaromatic in T1 according to energetic and electronic indices, while magnetic descriptors suggest it to have about two thirds the Baird‐aromaticity of T1 state COT ( 3 COT ). The extent of Baird‐aromaticity of intermediate BN/CC isosteres also varies markedly with aromaticity aspect considered. The strong aromaticity of 3 B 4 N 4 COT‐A according to magnetic descriptors can be linked to the symmetries of the orbitals involved in the virtual transitions from occupied to unoccupied orbitals, which describe the response of a molecule in an external magnetic field. However, the magnetic aspect of T1 state Baird‐aromaticity (response aromaticity) is not related to the electronic and energetic aspects (intrinsic aromaticity), findings that underline earlier observations on differences between the various aspects of the aromaticity phenomenon (or phenomena). Abstract : The Baird‐aromatic character of the T1 states of BN/CC cyclooctatetraene isosteres cannot be determined unambiguously as the results depend on aromaticity aspect considered. We clarify why, and stress that the magnetic aspect of aromaticity is a response aromaticity that differs from the intrinsic aromaticity represented by the electronic, energetic and geometric aspects.